Synthesis of 2-(1,2,4-oxadiazol-5-yl)-2,3-dihydro-4H-chromen-4-ones - Kysil, Andrii; Biitseva, Angelina; Bugera, Oleksandra; Yegorova, Tetyana; Voitenko, Zoia (Київський національний університет імені Тараса Шевченка, 2020)
Simple and efficient synthesis of 2-(1,2,4-oxadiazol-5-yl)-2,3-dihydro-4H-chromen-4-ones is elaborated. The method relies on CDI-mediated cyclocondensation of substituted 4-oxochromane-2-carboxylic acids and amidoximes. The protocol allows the preparation of 2-oxadiazolylchromanones decorated with two pharmacophores (2,3-dihydro-4H-chromen-4-one and 1,2,4-oxadiazole) that are in high demand in drug discovery.
Keywords: flavanone; 2-heteroaryl-4-chromanones; 4-oxadiazole; fluorine; 1'-carbonyldiimidazole (CDI)